Statistical Λ-Convergence in Probabilistic Normed Spaces. (19th March 2017) - Aldhaifallah, M.; Nisar, K. S.; Srivastava, H. M.; Mursaleen, M.
Abstract : The main objective of the study was to understand the notion of Λ-convergence and to study the notion of probabilistic normed ( P N ) spaces. The study has also aimed to define the statistical Λ-convergence and statistical Λ-Cauchy in PN-spaces. The concepts of these approaches have been defined by some examples, which have demonstrated the concepts of statistical Λ-convergence and statistical Λ-Cauchy in PN-spaces. Previous studies have also been used to understand similar terminologies and notations for the extraction of outcomes.